Exploring the effectiveness of tasks in problem-based learning as an instructional approach of learning among science and technology students of Universiti Tun Hussein Onn, Malaysia - Abdul Kadir, Zulida; Abdullah, Nor Hazana; Anthony, Elizabeth M.; Mohd Salleh, Berhannudin; Kamarulzaman, Robijah (UTHM Publisher, 2017)
The purpose of the paper is to explore the effectiveness of tasks in Problem-based Learning among Science and Technology students of Universiti Tun Hussein Onn, Malaysia. Data were collected from the respondents using inter-raters’ assessments scores on the tasks given, involving 25 respondents. The assessments are based on accuracy and quality of solving the tasks. The results indicated that students’ ability to solve the tasks is increasing from task 1 to task 4 from the aspect of accuracy (M=6.48, SD=0.432 to M=7.80, SD= 0.190) but slightly decrease for task 4 for quality (M=5.82, SD=0.881 to M=7.52, SD=0.789 for task 1 to 3, and M=7.16, SD=0.666 for task 4). The findings of the present study might be useful to lecturers and teachers in helping them to plan interventions in enhancing students’ ability to solve tasks at different levels.